2001
DOI: 10.1080/cmt.4.1.19.27
|View full text |Cite
|
Sign up to set email alerts
|

Perimenopausal women in estrogen vasomotor trials: contribution to placebo effect and efficacy outcome

Abstract: Perimenopausal women contributed to a higher placebo response, compared with the rate of response previously reported in clinical studies of estrogen replacement in postmenopausal women. Including perimenopausal women in future vasomotor symptom trials will require study populations of sufficient size to maintain the statistical power to demonstrate a difference between therapeutic response to active or placebo treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
(21 reference statements)
2
7
0
2
Order By: Relevance
“…Perimenopausal women may have contributed to a higher placebo response than postmenopausal women [66]. The mean placebo effect in all included trials dealing with soy supplements was 27%, which is in line with reported average values by Sloan et al of 20 to 30% after 4 wks [23].…”
Section: Discussionsupporting
confidence: 65%
“…Perimenopausal women may have contributed to a higher placebo response than postmenopausal women [66]. The mean placebo effect in all included trials dealing with soy supplements was 27%, which is in line with reported average values by Sloan et al of 20 to 30% after 4 wks [23].…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, it is important to subtract the placebo effect when interpreting the results of these studies. There is evidence to suggest that women who are perimenopausal may contribute to a higher placebo response rate in trials of hot flashes [30]. Fourth, several risk factors for the occurrence and severity of VMS, such as obesity, race, and smoking, have been neglected in evaluating the efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In the perimenopause, an assessment of hot flashes is complicated by the natural fluctuations in symptom frequency and severity during this transition. One study has shown that perimenopausal women show a higher placebo response in HT trials than postmenopausal women [10]. Studies included both naturally and surgically menopausal women.…”
Section: Population Being Studiedmentioning
confidence: 99%